Structural changes of agroindustrial production in Ukraine: The impact of external effects - Omelchenko, O.Y. (Економічний вісник Донбасу, 2010)
In the article influence of external effects is examined on the agroindustrial production of Ukraine. It show the dynamics of structural changes of agroindustrial production of Ukraine concerning its separate elements, which serves as investigation of external effects. It states in the article, that for providing of the positive structural changes of agroindustrial production the exposure of interconnection of structural changes and efficiency of the economic growth are needed. It is recommended for domestic enterprises during process of strategy determination to take into account influence of different external effects. Key words: external effects, agroindustrial production of Ukraine, a structure of production, structural changes. У статті розглядається вплив зовнішніх ефектів на агропромислове виробництво України. Показана динаміка структурних змін агропромислового виробництва України по її окремим складовим, яка є наслідком зовнішніх ефектів. В статті наголошується, що для забезпечення позитивних структурних змін агропромислового виробництва необхідно виявлення взаємозв’язку структурних змін і ефективності економічного росту. Вітчизняним підприємствам пропонується при визначенні своєї стратегії враховувати вплив різних зовнішніх ефектів. Ключові слова: зовнішні ефекти, агропромислове виробництво України, структура виробництва, структурні зміни. В статье рассматривается влияние внешних эффектов на агропромышленное производство Украины. Показана динамика структурных изменений агропромышленного производства Украины по ее отдельным составляющим, которая является следствием внешних эффектов. В статье отмечается, что для обеспечения положительных структурных изменений агропромышленного производства необходимо выявление взаимосвязи структурных изменений и эффективности экономического роста. Отечественным предприятиям рекомендуется при определении своей стратегии учитывать влияние различных внешних эффектов. Ключевые слова: внешние эффекты, агропромышленное производство Украины, структура производства, структурные изменения.